MESOPOROUS CERIUM OXIDE LOADED PdCu NANOPARTICLE CATALYST AND PREPARING METHOD THEREOF, AS WELL AS METHOD FOR PREPARING ENOLS USING THE SAME, AND ENOLS
The mesoporous cerium oxide supported PdCu nanoparticle catalyst addresses the heterogeneity and preparation challenges of current catalysts by anchoring PdCu alloy nanoparticles within mesoporous cerium oxide pores, achieving high selectivity and stability for enol synthesis.
Patent Information
- Application Number
- JP2024160805
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-25
- Filing Date
- 2024-09-18
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Current catalysts for selective hydrogenation of alkynols suffer from heterogeneity of active sites, leading to inefficient enol synthesis and complications in catalyst preparation, including waste discharge and complexity.
A mesoporous cerium oxide supported PdCu nanoparticle catalyst is developed using a porous organic polymer template, where PdCu alloy nanoparticles are anchored within the mesoporous cerium oxide pores, enhancing selectivity and simplifying the preparation process.
The catalyst achieves high selectivity (>99%) and stability for enol synthesis from alkynols, with a specific surface area of 68 m^2/g and pore size distribution of 5-60 nm, allowing for efficient and environmentally friendly production.
Smart Images

Figure 2025054212000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of catalyst technology, in particular to a mesoporous cerium oxide supported PdCu nanoparticle catalyst and its preparation method and use. [Background technology]
[0002] The selective hydrogenation of alkynols is a major route to synthesize enols such as linalool, isophytol, 2-methyl-3-buten-2-ol, cis-3-hexen-1-ol (leaf alcohol), and cis-2-butene-1,4-diol, which are important intermediates in the industrial production of high-value-added pharmaceuticals, agricultural chemicals, and fragrances. However, the process of obtaining enols by selective hydrogenation of alkynols is difficult, and in addition to protecting other functional groups such as C-OH in the alkynol molecule, more importantly, it is necessary to avoid overhydrogenation from C≡C to CC and selectively generate C=C instead.
[0003] In recent years, interest and research in the selective hydrogenation of alkynes and alkynols has led to the development of various metal-supported catalysts (such as Pd, Pt and Ni) to catalyze such reactions (Non-Patent Document 1). However, these metal-supported catalysts usually have large metal nanoparticles with a wide particle size distribution range, so that the metal active sites expose different crystal faces with different atomic structures. The heterogeneity of the active sites leads to differences in the selectivity of the catalytic reaction, as it leads to differences in the interactions between the reactants and the metal active sites in the alkynyl hydrogenation process (Non-Patent Document 2).
[0004] Mesoporous materials are important support materials for constructing supported hydrogenation catalysts, and mesoporous cerium oxide nanomaterials have a high specific surface area and abundant porous structure, and are importantly used in fields such as industrial catalysts, fuel cells, and sensor devices. At present, mesoporous cerium oxide support materials with high surface area are mainly prepared by using mesoporous carbon or mesoporous SiO2 as a hard template, using pluronic P123 or F127 as a soft template, the sol-gel method, and hydrothermal synthesis (Non-Patent Document 3). At present, these methods for preparing mesoporous cerium oxide supports have problems such as a large amount of waste liquid discharged during the preparation process and complicated preparation.
[0005] In view of the above-mentioned selective hydrogenation of alkynols and the current technical bottlenecks in the research field of high surface area mesoporous cerium oxide catalytic materials, the development of an efficient mesoporous cerium oxide-supported catalyst for highly selectively catalyzing the hydrogenation of alkynols to synthesize enols is of great significance. [Prior art documents] [Non-patent literature]
[0006] [Non-Patent Document 1] Catalysis Science&Technology,2020,10(2):327-331 [Non-Patent Document 2] Chemical Reviews,2020,120(2):683-733 [Non-Patent Document 3] Journal of Colloid and Interface Science,436(2014)52-62 Summary of the Invention [Problem to be solved by the invention]
[0007] In response to the above-mentioned problems of the prior art, the present invention proposes a mesoporous cerium oxide supported PdCu nanoparticle catalyst and its preparation method and use. The present invention adopts a method in which a porous organic polymer is used as a template, the pores of which are filled with PdCu alloy nanoparticles and cerium salt precursor in advance, the polymer template is removed by calcination, and then the catalyst is reduced to obtain a catalyst in which PdCu alloy is anchored in the pores of mesoporous cerium oxide, and the catalyst is used to selectively catalyze the hydrogenation of alkynol to prepare enol. The reaction formula is as follows: [ka] [Means for solving the problem]
[0008] In order to achieve the above object, the present invention provides the following technical scheme.
[0009] Technical scheme 1: A mesoporous cerium oxide-supported PdCu nanoparticle catalyst, in which the mass ratio of each component in the mesoporous cerium oxide-supported PdCu nanoparticle catalyst is Pd:Cu:CeO2=(1-4):(1-4):100. The specific surface area of the mesoporous cerium oxide-supported PdCu nanoparticle catalyst is 68 m 2 / g, pore size distribution is 5-60 nm, pore volume is 0.3 cm 3 / g.
[0010] "Active site isolation" refers to isolating the active sites of metals to homogenize them and suppress side reactions that may be caused by metal agglomeration, thereby enhancing the selectivity of the catalyst during the catalytic reaction. In the present invention, the composition and structure of the metal active sites in the catalyst are adjusted by using the second metal copper as a regulator. In bimetallic or multimetallic nanoparticles, the interaction between the components changes the composite structure of the catalytic site, and the electronic structure of the active metal changes in the form of charge transfer or the like. These two influencing factors determine the binding mode and strength of the reactants / intermediates / products at the active sites, which directly affects the selectivity of the catalyst. As a metal with high electron density and low cost, the present invention dopes Cu as the second metal to change the properties of the active metal.
[0011] Technical scheme 2: A method for preparing mesoporous cerium oxide-supported PdCu nanoparticle catalyst, which involves using melamine and phthalaldehyde to carry out an aldehyde-amine polycondensation reaction to obtain porous organic polymer template materials (POFs), filling the pores of the porous organic polymer template materials with PdCu alloy nanoparticles and cerium salt precursors, and calcining to remove the template agent to obtain mesoporous cerium oxide-supported PdCu nanoparticle catalyst.
[0012] In addition, the preparation method specifically includes the following steps: weigh melamine and phthalaldehyde to carry out aldehyde-amine polycondensation reaction to obtain a porous organic polymer template material; ultrasonically disperse the porous organic polymer template material in a mixed aqueous solution of palladium acetate and copper nitrate, dropwise add sodium borohydride solution to reduce, obtain a PdCu bimetallic nanoparticle PdCu-POFs material; ultrasonically disperse the PdCu-POFs material in an aqueous solution of cerium nitrate, slowly dropwise add NaOH solution under vigorous stirring, react for 3 hours, remove the solvent by suction filtration, dry the obtained solid sample, and then put it into a muffle furnace to heat up to 600 ° C at a rate of 4 ° C / min in an argon atmosphere and calcinate for 2 hours, then calcinate at 600 ° C in air for 2 hours, cool down to 400 ° C and reduce with H2 / Ar for 2 hours to prepare a PdCu-CeO2 catalyst.
[0013] Furthermore, the method for preparing the porous organic polymer template material is to add 5 g of melamine (99%) and 8 g of phthalaldehyde (99%) to 250 mL of dimethyl sulfoxide (99%), heat to 180°C at a rate of 20°C / min in an argon atmosphere, and react with stirring at this temperature for 72 hours, then remove the solvent by suction filtration, wash the yellow solid sample with ethanol three times, and vacuum dry at 80°C for 6 hours to prepare a porous organic polymer POFs material.
[0014] Furthermore, the mass ratio of the PdCu-POFs material to cerium nitrate is 1:2.6. The aqueous solution of cerium nitrate is prepared by dissolving 2.6 g of cerium nitrate in 50 mL of water.
[0015] Technical scheme 3: A method for preparing enol, using alkynol as raw material, the mesoporous cerium oxide supported PdCu nanoparticle catalyst as catalyst, ethanol as solvent, and catalytic reaction under normal pressure and room temperature hydrogen atmosphere to obtain enol. The catalytic active site in the catalytic hydrogenation reaction of the catalyst is PdCu alloy nanoparticle, and the control of the electronic performance of active metal Pd by Cu can significantly improve the selectivity of the reaction product. The conversion rate of alkynol and the selectivity of enol are detected by gas chromatography or gas chromatography mass spectrometry analysis, and the conversion rate of alkynol can reach 100%, the selectivity of enol is higher than 99%, and the catalyst can be stably applied (recycled) at least 5 times.
[0016] The ratio of the amount of the alkynol to the amount of the mesoporous cerium oxide-supported PdCu nanoparticle catalyst used was 1 mmol:10 mg, and the pressure of the hydrogen was 1 atm.
[0017] Technical Scheme 4: Enols prepared using the preparative methods described above. Effect of the Invention
[0018] Compared with the prior art, the present invention has the following advantages and technical effects:
[0019] 1. The PdCu-CeO2 catalyst prepared in this invention utilizes the POFs template sacrificial method to give the catalyst a high specific surface area and a wide pore size distribution, and uses Cu metal as the second metal to adjust the electronic structure of the active metal Pd and the composition of the active sites, thereby improving the selectivity of enol synthesis from alkynol hydrogenation.
[0020] 2. Using alkynol as raw material and hydrogen as reducing agent, enol is synthesized by selective catalytic hydrogenation at room temperature and pressure using PdCu-CeO2 catalyst. The reaction temperature is room temperature, and no toxic and harmful waste is discharged during the reaction process, making this method of synthesizing alkynol by selective catalytic hydrogenation more environmentally friendly.
[0021] 3. The mesoporous PdCu-CeO2 catalyst provided in the present invention and the method for catalyzing the selective catalytic hydrogenation of alkynol to synthesize enol using the same are simple to operate, easy to control, have high product selectivity, are green economical, and easy to scale up industrially. [Brief description of the drawings]
[0022] The drawings constituting a part of this application are intended to provide a further understanding of the application, and the illustrative embodiments and the description thereof are intended to explain the application and are not to be construed as unduly limiting the application. [Figure 1] FIG. 2 is a transmission electron microscope photograph of the PdCu-CeO2 catalyst prepared in Example 1 of the present invention, where (a) and (b) are transmission electron microscope photographs at different magnifications, and (c) is a dark-field transmission electron microscope photograph of the PdCu-CeO2 catalyst. [Diagram 2] FIG. 2 is a diagram showing the nitrogen adsorption / desorption and pore size distribution of the PdCu-CeO2 catalyst prepared in Example 1 of the present invention. [Diagram 3] The reuse effect diagram of the PdCu-CeO2 catalyst prepared in Example 3 of the present invention DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Various exemplary embodiments of the present invention will now be described in detail, however this detailed description is not to be construed as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, features and embodiments of the present invention.
[0024] It should be understood that the terms described herein are only for describing particular embodiments and are not intended to limit the present invention. Also, the numerical ranges in the present invention should be understood to be specifically disclosed at every intermediate value between the upper and lower limits of the range. Each subrange between any stated value or intermediate value in the stated range, as well as any other stated value or intermediate value in the range, is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the range.
[0025] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention describes. Although the present invention describes only preferred methods and materials, methods and materials similar or equivalent to those described herein can also be used in the practice or testing of the present invention. All publications mentioned herein are incorporated by reference to disclose and describe the methods and / or materials related thereto. In the event of any conflict with any incorporated publication, the contents of this specification control.
[0026] It will be apparent to those skilled in the art that many modifications and variations can be made to the specific embodiments of the present specification without departing from the scope or spirit of the present invention. Other embodiments of the present specification will be apparent to those skilled in the art. The present specification and examples are illustrative only.
[0027] As used herein, the terms "including," "comprising," "having," "containing," and the like are all open-ended terms, meaning including but not limited to.
[0028] In the present invention, "room temperature" refers to 20°C unless otherwise specified.
[0029] All of the raw materials used in the following examples of the present invention are commercially available.
[0030] The present invention provides a method for preparing mesoporous cerium oxide-supported PdCu nanoparticle catalyst, which mainly uses melamine and phthalaldehyde to carry out aldehyde-amine polycondensation reaction to obtain porous organic polymer template materials (POFs), fill the pores of the porous organic polymer template materials with PdCu alloy nanoparticles and cerium salt precursors, calcinate to remove the POFs template, and reduce to prepare PdCu-CeO2 catalyst with PdCu nanoparticles anchored in the pores of mesoporous cerium oxide.
[0031] The method for preparing the porous organic polymer template material is to add 5 g of melamine (active ingredient 99%) and 8 g of phthalaldehyde (active ingredient 99%) to 250 mL of dimethyl sulfoxide (active ingredient 99%), heat to 180°C at a rate of 20°C / min in an argon atmosphere, and react with stirring at this temperature for 72 hours. After that, the solvent is removed by suction filtration, the yellow solid sample is washed three times with ethanol, and vacuum dried at 80°C for 6 hours to prepare the porous organic polymer POFs material.
[0032] The preparation method of the PdCu-CeO2 catalyst is as follows: 1g of POFs material is ultrasonically dispersed in a mixed aqueous solution of palladium acetate and copper nitrate, and reduced by dripping dilute solution of sodium borohydride to obtain PdCu bimetallic nanoparticle PdCu-POFs material; 2.6g of Ce(NO3)3·6H2O is dissolved in 50mL of water, and then 1g of PdCu-POFs is added to the solution; the mixture is ultrasonically treated for 60 minutes, and then NaOH solution is slowly dripped while vigorously stirring, reacting for 3 hours, filtered to remove the solvent, and the obtained solid sample is dried, and then placed in a muffle furnace and heated to 600°C at a rate of 4°C / min in an argon atmosphere and calcined for 2 hours, then calcined at 600°C in air for 2 hours, cooled to 400°C, and reduced with a H2 / Ar mixture with a volume ratio of 1:3 for 2 hours to prepare the PdCu-CeO2 catalyst.
[0033] The specific surface area of the prepared PdCu-CeO2 catalyst is 68 m 2 / g, pore size distribution is 5-60 nm, pore volume is 0.3 cm 3 / g. The mass ratio of each component in the PdCu-CeO2 catalyst is Pd:Cu:CeO2=(1-4):(1-4):100. Preferably, it is 2:2:100.
[0034] The prepared PdCu-CeO2 catalyst, alkynol, and solvent ethanol are placed in a reactor, and hydrogen at normal pressure is supplied as the hydrogen source to carry out the catalytic reaction at room temperature to obtain enol. In the reaction process of the synthesis of enol by selective catalytic hydrogenation of said alkynol, the hydrogen pressure is 1 atm, and the reaction temperature is room temperature. When the conversion rate of alkynol and the selectivity of enol are detected by the analysis of gas chromatography or gas chromatography mass spectrometer, the conversion rate of alkynol can reach 100%, the selectivity of enol is higher than 99%, and the catalyst can be stably recycled at least five times. The catalytic active site of this catalytic hydrogenation reaction is PdCu alloy nanoparticles, and the control of the electronic performance of the active metal Pd by Cu can significantly improve the selectivity of the reaction product.
[0035] The following examples are further illustrations of the technical scheme of the present invention.
[0036] Example 1
[0037] Preparation of mesoporous cerium oxide supported PdCu nanoparticle catalysts
[0038] 1) Preparation of POFs template material: 5 g of melamine (99%) and 8 g of phthalaldehyde (99%) are added to 250 mL of dimethyl sulfoxide (99%), heated to 180 °C at a rate of 20 °C / min in an argon atmosphere, and reacted at this temperature with stirring for 72 hours. After that, the solvent is removed by suction filtration, the yellow solid sample is washed three times with ethanol, and vacuum dried at 80 °C for 6 hours to prepare a porous organic polymer POFs material.
[0039] 2) Preparation of PdCu-CeO2 catalyst: 1g of POFs material was ultrasonically dispersed in 10mL of a mixed aqueous solution of palladium acetate and copper nitrate (mass ratio of palladium acetate, copper nitrate and water 0.002:0.002:1), and reduced by dropping 2mL of a dilute solution of sodium borohydride with a concentration of 0.1mol / L to obtain 1g of PdCu bimetallic nanoparticle PdCu-POFs material. 2.6g of Ce(NO3)3·6H2O was dissolved in 50mL of water, and then 1g of PdCu-POFs was added to the solution and mixed. After treating the mixture with ultrasonic waves for 60 minutes, slowly drop 10 mL of 2 mol / L NaOH solution while vigorously stirring, react for 3 hours, filter to remove the solvent, dry, heat to 600°C at a rate of 4°C / min in an argon atmosphere and calcinate for 2 hours, then calcinate at 600°C in air for 2 hours, cool to 400°C and reduce with H2 / Ar (volume ratio 1:3) for 2 hours to prepare 1 g of PdCu-CeO2 catalyst with a mass ratio of Pd:Cu:CeO2 = 2:2:100.
[0040] FIG. 1 shows the transmission electron microscope photographs of the PdCu-CeO2 catalyst prepared in Example 1 of the present invention, where (a) and (b) are transmission electron microscope photographs at different magnifications, and (c) is a dark-field transmission electron microscope photograph of the PdCu-CeO2 catalyst. As can be seen from the figure, Pd and Cu elements are uniformly distributed on the CeO2 support.
[0041] FIG. 2 is a graph showing the nitrogen adsorption / desorption and pore size distribution of the PdCu-CeO2 catalyst prepared in Example 1 of the present invention. As can be seen from the graph, the specific surface area of the prepared PdCu-CeO2 catalyst is 68 m 2 / g, pore size distribution is 5-60 nm, pore volume is 0.3 cm 3 / g.
[0042] Example 2
[0043] Method for preparing enol by catalyzing selective hydrogenation of alkynol: 10 mg of PdCu-CeO2 catalyst prepared in Example 1 and 1 mmol of ethoxypropargyl alcohol are placed in a 10 mL round-bottom flask containing 5 mL of anhydrous ethanol, and hydrogen is passed through at normal pressure, and the reaction is stirred at 70°C. The product yield is detected by gas chromatography analysis. After 60 minutes of reaction, the conversion rate of ethoxypropargyl alcohol is 94%, and the selectivity of the product ethoxypropynyl alcohol is 98%.
[0044] Example 3
[0045] The PdCu-CeO2 catalyst recovered from the filtration in Example 2 is used to recatalyze the selective hydrogenation of alkynol to prepare enol, and the specific method is as follows:
[0046] The recovered PdCu-CeO2 catalyst and 1 mmol of ethoxypropargyl alcohol were placed in a 10 mL round-bottom flask containing 5 mL of ethanol, and hydrogen was passed through at normal pressure and reacted at 70°C with stirring. The product yield was detected by gas chromatography analysis. The PdCu-CeO2 catalyst was used five times (each reaction time was 60 min), and the conversion rate of ethoxypropargyl alcohol was higher than 90% in each case, and the selectivity of ethoxypropynyl alcohol was higher than 95% in each case (see Figure 3).
[0047] Example 4-11
[0048] The PdCu-CeO2 catalyst prepared in Example 1 was used to catalyze the selective hydrogenation reaction of various alkynols, and the specific method is as follows:
[0049] 10 mg of PdCu-CeO2 catalyst and 1 mmol of alkynol were placed in a 10 mL round-bottom flask containing 5 mL of ethanol, and hydrogen was passed through at normal pressure and reacted at 70°C with stirring. The product yield was detected by gas chromatography analysis. The specific reaction results are shown in Table 1.
[0050] [Table 1]
[0051] The PdCu-CeO2 catalyst prepared in this example was used to catalyze the selective catalytic hydrogenation reaction of alkynol. The specific method was the same as that in Example 2. The results showed that the reaction conversion rate was higher than 98%, and the product selectivity was 90%.
[0052] Example 12
[0053] The procedure is the same as in Example 1, except that 1.7 g of Ce(NO3)3·6H2O was dissolved in 50 mL of water, and then 0.5 g of the PdCu-POFs prepared in Example 1 was added to the solution to obtain a PdCu-CeO2 catalyst (mass ratio of each component: Pd:Cu:CeO2 = 1:1:100).
[0054] The PdCu-CeO2 catalyst prepared in this example was used to catalyze the selective catalytic hydrogenation of ethoxypropargyl alcohol to synthesize ethoxypropynyl alcohol, the specific method being the same as in Example 2, and the results showed that the reaction conversion rate was 86%, and the product selectivity was 98%.
[0055] Example 13
[0056] The procedure is the same as in Example 1, except that 1.7 g of Ce(NO3)3·6H2O was dissolved in 50 mL of water, and then 1.5 g of the PdCu-POFs prepared in Example 1 was added to the solution to obtain a PdCu-CeO2 catalyst (mass ratio of each component: Pd:Cu:CeO2 = 3:3:100).
[0057] The PdCu-CeO2 catalyst prepared in this example was used to catalyze the selective catalytic hydrogenation of ethoxypropargyl alcohol to synthesize ethoxypropynyl alcohol, the specific method being the same as in Example 2, and the results showed that the reaction conversion rate was 99%, and the product selectivity was 92%.
[0058] Example 14
[0059] The procedure is the same as in Example 1, except that 1.7 g of Ce(NO3)3·6H2O was dissolved in 50 mL of water, and then 2 g of the PdCu-POFs prepared in Example 1 was added to the solution to obtain a PdCu-CeO2 catalyst (mass ratio of each component: Pd:Cu:CeO2 = 4:4:100).
[0060] The PdCu-CeO2 catalyst prepared in this example was used to catalyze the selective catalytic hydrogenation of ethoxypropargyl alcohol to synthesize ethoxypropynyl alcohol, the specific method being the same as in Example 2, and the results showed that the reaction conversion rate was 100%, and the product selectivity was 87%.
[0061] Comparative Example 1
[0062] Same as Example 1, except that palladium acetate is replaced with an equal amount of platinum acetate.
[0063] The catalyst prepared in this comparative example was used to catalyze the selective catalytic hydrogenation reaction of alkynol. The specific method was the same as in Example 2. The results showed that the reaction conversion rate was higher than 85%, and the product selectivity was 95%.
[0064] Comparative Example 2
[0065] Same as Example 2, except that copper nitrate is replaced with an equal amount of palladium acetate.
[0066] The palladium-supported catalyst prepared in this comparative example was used to catalyze the selective catalytic hydrogenation reaction of alkynol, and the specific method was the same as that in Example 2. The results showed that the reaction conversion rate was higher than 99%, and the product selectivity was 84%.
[0067] Comparative Example 3
[0068] The same as Example 2, except that the amount of PdCu-CeO2 catalyst added was 8 mg.
[0069] The PdCu-CeO2 catalyst prepared in this comparative example was used to catalyze the selective catalytic hydrogenation reaction of alkynol, and the results showed that the reaction conversion was higher than 86% and the product selectivity was 98%.
[0070] The above are only preferred specific embodiments of the present application, but the scope of protection of the present application is not limited thereto, and any changes or replacements that a person skilled in the art can easily conceive within the technical scope disclosed in the present application should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application shall be subject to the scope of the claims.
Claims
1. A mesoporous cerium oxide-supported PdCu nanoparticle catalyst, wherein the mass ratio of each component in the mesoporous cerium oxide-supported PdCu nanoparticle catalyst is Pd:Cu:CeO 2 = (1-4):(1-4):
100.
2. The specific surface area of the mesoporous cerium oxide supported PdCu nanoparticle catalyst is 68 m 2 / g, pore size distribution is 5-60 nm, pore volume is 0.3 cm 3 The mesoporous cerium oxide supported PdCu nanoparticle catalyst according to claim 1, wherein the PdCu nanoparticle catalyst has a molecular weight of 1000 to 10000 g / g.
3. 2. The method for preparing the mesoporous cerium oxide-supported PdCu nanoparticle catalyst according to claim 1, comprising the steps of: carrying out an aldehyde-amine polycondensation reaction using melamine and phthalaldehyde to obtain a porous organic polymer template material; filling the pores of the porous organic polymer template material with PdCu alloy nanoparticles and a cerium salt precursor; and calcining the mixture to remove the template agent to obtain the mesoporous cerium oxide-supported PdCu nanoparticle catalyst.
4. The method of loading the PdCu alloy nanoparticles and the cerium salt precursor is specifically as follows: The porous organic polymer template material is ultrasonically dispersed in a mixed aqueous solution of palladium acetate and copper nitrate, and reduced by dropping a sodium borohydride solution to obtain a PdCu-POFs material of PdCu bimetallic nanoparticles; 4. The method for preparing a mesoporous cerium oxide supported PdCu nanoparticle catalyst according to claim 3, comprising the steps of ultrasonically dispersing a PdCu-POFs material in an aqueous solution of cerium nitrate, dropping an NaOH solution into the aqueous solution while stirring, reacting for 3 hours, removing the solvent by suction filtration, and drying the obtained solid sample.
5. The firing method was as follows: the temperature was raised to 600° C. in an argon atmosphere and the temperature was raised to 600° C. in an air atmosphere, and the firing was performed for 2 hours. Then, the temperature was lowered to 400° C. and the mixture was heated in H 2 The method for preparing the mesoporous cerium oxide supported PdCu nanoparticle catalyst according to claim 3, further comprising reducing the catalyst with Ar / Ar.
6. The method for preparing mesoporous cerium oxide supported PdCu nanoparticle catalyst according to claim 3, wherein the mass ratio of melamine to phthalaldehyde is 5:
8.
7. The method for preparing mesoporous cerium oxide supported PdCu nanoparticle catalyst according to claim 4, wherein the mass ratio of the PdCu-POFs material to cerium nitrate is 1:2.
6.
8. A method for preparing an enol, comprising: using an alkynol as a raw material; and using the mesoporous cerium oxide-supported PdCu nanoparticle catalyst according to claim 1 as a catalyst; and carrying out a catalytic reaction in a hydrogen atmosphere at room temperature and atmospheric pressure using ethanol as a solvent to obtain an enol.
9. The preparation method according to claim 8, wherein the ratio of the alkynol to the mesoporous cerium oxide supported PdCu nanoparticle catalyst is 1 mmol:10 mg.
10. 9. An enol prepared by the process of claim 8.
Citation Information
Patent Citations
Supported catalyst, and preparation method and application thereof
CN110860284A
Hydrogenation catalyst and its use in partial hydrogenation of 1,4-butynediol
GB832141A
Porous cerium oxide with lamellar structure, its preparation and its use in catalytic reactions
JP1999501898A
Methanol synthesis and cracking catalyst, its production and methanol synthesis and cracking method
JP2001079398A
Method for manufacturing carried bimetal alloy
JP2020168588A